The Relationship Between Dry Eye Syndrome And Digital Screen Use - Sabnam Banu, Anchal Rathore, Deepan Roka, Sabitha Vibash (Journal of Neonatal Surgery, 2025)
Using digital screens, also known as VDTs (visual display terminals) for extended periods of time each day has become a need in today’s world, involving a variety of tasks in work, school and leisure contexts. Dry eyes are the most common problem occurring with extended use of digital screens. Dry eyes arise when there is insufficient production of tears in either quality or quantity to maintain the eyes moisturized and comfortable. In order to lessen the screen related vision impairment and issues, we examine the link between digital screen use and dry eyes and also increase the awareness of this issue. A combination of multiple factors led to a notable increase in the prevalence of dry eye illness during the COVID-19 pandemic.